2009
DOI: 10.1029/2008ja013128
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic‐electron dropouts and recovery: A superposed epoch study of the magnetosphere and the solar wind

Abstract: [1] During 124 high-speed-stream-driven storms from two solar cycles, a multispacecraft average of the 1.1-1.5 MeV electron flux measured at geosynchronous orbit is examined to study global dropouts of the flux. Solar wind and magnetospheric measurements are analyzed with a superposed epoch technique, with the superpositions triggered by storm-convection onset, by onset of the relativistic-electron dropouts, and by recovery of the dropouts. It is found that the onset of dropout occurs after the passage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(170 citation statements)
references
References 143 publications
5
165
0
Order By: Relevance
“…Here we use the definition of dropouts described in Turner et al [2012b], which includes both adiabatic effects and nonadiabatic losses. , possibly within plasmaspheric plumes that form during active periods and span the radial extent of the outer radiation belt [Borovsky and Denton, 2009]. Typically, only electrons with energy >~2 MeV can resonate with EMIC waves [Meredith et al, 2003], though during very active conditions this resonant energy limit might decrease to~400 keV [Ukhorskiy et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Here we use the definition of dropouts described in Turner et al [2012b], which includes both adiabatic effects and nonadiabatic losses. , possibly within plasmaspheric plumes that form during active periods and span the radial extent of the outer radiation belt [Borovsky and Denton, 2009]. Typically, only electrons with energy >~2 MeV can resonate with EMIC waves [Meredith et al, 2003], though during very active conditions this resonant energy limit might decrease to~400 keV [Ukhorskiy et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms resulting in atmospheric loss include pitch-angle scattering through wave particle interactions with magnetospheric plasma waves 13 and violation of the first adiabatic invariant due to highly stretched magnetotail fields (that is, those in which the field line curvature becomes comparable to the particle's gyro-radius 14 ). Several recent statistical studies have concluded that losses to the atmosphere are probably responsible for main phase 5,11 and recovery phase 15,16 electron loss during certain types of geomagnetic storms. However, the mainphase dropout results were inferred in those studies, with no clear observations showing that the primary loss was to the atmosphere.…”
mentioning
confidence: 99%
“…Electromagnetic ion cyclotron (EMIC) waves can lead to very rapid pitch angle diffusion of relativistic electrons, and are expected to be proximate to the plasmapause (Summers et al, 1998;Li et al, 2007). Borovsky and Denton (2009) found from a study of geosynchronous data that dropouts, attributed to EMIC waves, coincide with the formation of a plasmaspheric drainage plume, in conjunction with a dense and hot plasma sheet. Usanova et al (2012Usanova et al ( , 2013 found from THEMIS and Cluster surveys that EMIC within plumes correlates with solar wind dynamic pressure, though the occurrence rate is still in the 5-10 % range inside of geosynchronous orbit.…”
Section: Radial Diffusion Simulationmentioning
confidence: 99%